Taxonomy of the monotypic genus Koehleria Cherbonnier, 1988 (Echinodermata: Holothuroidea: Cucumariidae) - Thandar, Ahmed S.; Samyn, Yves (Zootaxa, 2004)
Voucher material recently collected from the 2-Mile Reef at Sodwana Bay (Republic of South Africa), allows the evaluation of the monotypic genus Koehleria Cherbonnier, 1988 and its species K. unica Cherbonnier, 1988 collected from Tul ar (Madagascar). Cherbonnier s (1988) conclusion, that Koehleria is most related to the also monotypic genus Pseudocolochirus Pearson, 1910 is correct, but the differences between Koehleria and Pseudocolochirus are too small to justify the retention of Koehleria. Koehleria is relegated herein to the synonymy of Pseudocolochirus. Such a step decreases the velocity with which monotypic genera are currently described within the Dendrochirotida.